Answering critical questions on mining in the Philippines - Eligia D. Clemente; Sonny N. Domingo; Arvie Joy A. Manejar (Philippine Institute for Development Studies (PIDS), 2018)
To attain a perceived acceptable quality of life, the mining industry plays a crucial role as the demand for minerals and energy increases while ore quality decreases. On the other hand, the social and environmental footprints which mining companies leave behind are deemed unacceptable by the communities affected. In general, the concept of sustainable development where people are expected to take actions using leading technologies without compromising the ability of future generations to meet their own needs is placed in the backseat, with business interests at the front. This phenomenon is not limited to the Philippines but has been observed worldwide. The collaborative effort of stakeholders has crafted the Philippine Mining Act of 1995 to address the needs of both the company and the people it affects. By itself, the law is all encompassing and covers the triple bottom-line of sustainable development - the growth of the economy, environmental protection, and social responsibility. However, RA 7942 was not able to mitigate environmental degradation nor was it able to contribute to poverty alleviation and preservation of cultural communities. The implementation aspect also encountered problems since there has been institutional overlaps and lack of delineation of function between the Mines and Geosciences Bureau (MGB) and the Environmental Management Bureau. [...]
Keywords: 330; Philippine mining; sustainable development; social and environmental responsibility; bureaucracy; poverty alleviation; corruption; the triple bottom-line